HUBUNGAN MINAT BELAJAR TERHADAP KEMAMPUAN PENALARAN MATEMATIK SISWA SMP PADA MATERI LINGKARAN - Winda Awaliyah; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2018)
This research aims to determine the relationship of student learning interest to the mathematical reasoning ability of junior high school students in chapter circle. Method used is quantitative with correlation method. this research was conducted in one of junior high school in Cimahi with population of all students of class IX and sample IX-M as many as 30 people. Instrumen used in this research is a questionnaire instrument to measure the level of student learning interest and test instrument to measure the ability mathematical reasoning of students. Analysis results visible there is a significant relationship between student learning interests with the ability of mathematical reasoning and contribution/ influence interest in learning on the ability of mathematical reasoning of junior high school students of class IX is positive is equal to 74,64% while the remaining 25,36% influenced by other factors.